Interactions of Salmonella with animals and plants - Wiedemann, Agnès; Virlogeux-Payant, Isabelle; Chaussé, Anne-Marie; Schikora, Adam; Velge, Philippe (Frontiers in Microbiology, 2015)
Salmonella enterica species is a Gram negative bacterium, which is responsible for a wide range of food- and water-borne diseases in both humans and animals, thereby posing a major threat to public health. Recently, there has been an increasing number of reports, linking Salmonella contaminated raw vegetables and fruit with food poisoning. Many studies have shown that an essential feature of the pathogenicity of Salmonella is its capacity to cross a number of barriers requiring invasion of a large variety of cells and that the extent of internalization may be influenced by numerous factors. However, it is poorly understood how Salmonella successfully infects hosts as diversified as animals or plants. The aim of this review is to describe the different stages required for Salmonella interaction with its hosts: (i) attachment to host surfaces; (ii) entry processes; (iii), multiplication; (iv) suppression of host defence mechanisms ; and to point out similarities and differences between animal and plant infections.